2009
DOI: 10.1038/nn.2243
|View full text |Cite
|
Sign up to set email alerts
|

Wnt antagonism of Shh facilitates midbrain floor plate neurogenesis

Abstract: The floor plate, an essential ventral midline organizing center that produces the morphogen Shh, has distinct properties along the neuraxis. The neurogenic potential of the floor plate and its underlying mechanisms remain unknown. Using Shh as a driver for lineage analysis, we found that the mouse midbrain, but not the hindbrain, floor plate is neurogenic, giving rise to dopamine (DA) neurons. Distinct spatiotemporal Shh and Wnt expression may distinguish the neurogenetic potential of these structures. We disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
119
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(138 citation statements)
references
References 37 publications
16
119
1
2
Order By: Relevance
“…In particular, exposure to Wnt-1 resulted in a significant increase in the midbrain FP markers CORIN and NOV , as well as increases in the DA progenitor markers LMX1B, EN1 ,and NGN2 . These data are in agreement with previous studies showing that Wnt signaling is critical in the neurogenic response of the midbrain FP (Joksimovic et al, 2009). …”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…In particular, exposure to Wnt-1 resulted in a significant increase in the midbrain FP markers CORIN and NOV , as well as increases in the DA progenitor markers LMX1B, EN1 ,and NGN2 . These data are in agreement with previous studies showing that Wnt signaling is critical in the neurogenic response of the midbrain FP (Joksimovic et al, 2009). …”
Section: Resultssupporting
confidence: 94%
“…The FP is generally considered a non-neurogenic region. However, genetic lineage mapping studies in the mouse have recently reported that the midbrain FP selectively exhibits neurogenic potential and is the source of ventral midbrain dopamine neurons (Kittappa et al, 2007; Ono et al, 2007; Joksimovic et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Wnt2(Ϫ/Ϫ) mice displayed a decrease in the proliferative capacity of DA progenitors in the ventricular zone of the VM and in their capacity to undergo neurogenesis, as indicated by the reduction of postmitotic cells (Nurr1 ϩ and TH ϩ cells) in the DA lineage. Wnt1 has also been described to regulate progenitor proliferation in the developing VM (17,19) as well as the number of Nurr1 and TH ϩ cells in the VM (16,18,19). However, other features of the Wnt1(Ϫ/Ϫ) mutant were not phenocopied by the Wnt2(Ϫ/Ϫ) animals, indicating that each Wnt regulates a specific combination of functions, some of which are redundantly regulated by distinct Wnts.…”
Section: Discussionmentioning
confidence: 99%
“…This development process is orchestrated by key signaling molecules [eg, sonic hedgehog (SHH), fibroblast growth factor 8 (FGF8), and Wnt signals] secreted from neighboring organizers and their downstream intrinsic transcription factors (eg, Otx2, Lmx1a/b, Foxa1/2, Ngn2, Pitx3, and Nurr1) [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Importantly, some of these transcription factors have been successfully exploited for enhancing the generation of mDA neurons by their overexpression in stem cells.…”
mentioning
confidence: 99%